Evaluating different carriers of Metarhizium brunneum F52 microsclerotia for control of adult Asian longhorned beetles (Coleoptera: Cerambycidae). Issue 9 (1st September 2016) - Goble, Tarryn A.; Gardescu, Sana; Jackson, Mark A.; Hajek, Ann E.
ABSTRACT: Microsclerotia (MS) of Metarhizium brunneum strain F52 (Hypocreales: Clavicipitaceae) were processed as granules using three carriers: kaolin clay, microcrystalline cellulose (MCC), or diatomaceous earth (DE). In a series of experiments aimed at comparing viable conidial production, each MS carrier type was hydrated using a decreasing range of water activities on glycerol or polyethylene glycol (PEG200)-amended media. Conidial density and percent germination of conidia declined significantly as water activity was lowered. All three carrier types produced >2–6 × 10 9 viable conidia/gram at higher water activities ( а w >0.987) but were still capable of producing 2.9 × 10 7  ± 1.6 × 10 6 conidia/g (30% glycerol а w  = 0.883) and 1.9 × 10 7  ± 6.5 × 10 6 conidia/g (30% PEG200 а w  = 0.924) at the lowest tested water activities. MS carrier types were sprayed onto 0.4 m length logs with or without hydromulch formulation. The median survival times of Asian longhorned beetles, Anoplophora glabripennis (Coleoptera: Cerambycidae), exposed by climbing double the length of the logs of hydromulch-treated bark, were 16.5–20.5 d while beetles exposed to logs without hydromulch formulation had median survival times of 22–25.5 d. Overall, experiments showed that there were few biologically significant differences between the MS carrier types.